Quality and chemical stability of long-term stored soy, canola, and sunflower cold-pressed cake lipids before and after thermomechanical processing: A 1H NMR study. (1st January 2023) - Vidal, Natalia P.; Rahimi, Jamshid; Kroetsch, Benjamin; Martinez, Mario M.
Abstract: Oilseed cakes obtained by cold-pressing are rich in lipids susceptible to degradation, which could challenge their handling and nutritional, safety, and sensory requirements, especially during long-storage. Although extrusion is effective at reducing antinutritional factors, its effect on the lipid stability of oilseed cakes remains unknown. In this work, a comparative 1 H-NMR-based investigation of the lipid quality in terms of lipid composition, hydrolysis, and oxidation status, as well as their stability after long-term storage was performed on soybean, canola and sunflower cold-pressed cakes before and after low-moisture extrusion. Soybean cake was rich in linolenic and linoleic groups, whereas canola and sunflower mostly contained linoleic and monounsaturated acyl groups and fatty acids. Extrusion did not modify lipid quality immediately after processing. Nevertheless, lipid stability was significantly reduced after 12 months, especially in cakes subjected to extrusion, evidenced by the degradation of their polyunsaturated acyl groups and fatty acids, and the increase of primary and secondary oxidation products. Since lipid quality was retained immediately after extrusion (no storage), results indicated that any action to avoid the enzymatic lipid degradation must be performed immediately after cold-pressing. Moreover, long-term storage should be carefully considered as the lipid stability/quality of extruded cakes was compromised after extrusion. Highlights: Lipid quality was studied in terms of acyl group profile, hydrolysis, and oxidation. Cold-pressed cakes contain up to 18% lipids, most of which susceptible to degradation. NMR showed that extrusion did not modify lipid quality immediately after processing. Lipid stability was significantly reduced after 12 months, especially after extrusion.